2020
DOI: 10.1186/s42480-020-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Planning of Food-Energy-Water-Waste (FEW2) nexus for sustainable development

Abstract: It is critical for reliable infrastructure planning to address the Food-Energy-Water-Waste (FEW2) nexus at system level. This paper presents the applicability of resilience.io platform across water, energy and waste sectors (including food and agricultural waste) with focus on waste-to-energy pathway, aiming to establish the optimal FEW2 nexus based on economic and environmental indicators. A rich array of technology options, including water production facilities, clean energy technologies and waste-to-energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Triantafyllidis et al developed the platform named as resilience.io to evaluate urban infrastructural projects. In this twofold study, agent‐based models were first devised to model the dynamic population behaviors and obtain the estimated demand of resources, followed by mixed‐integer programming to determine the optimal investment and operating solutions, accounting for both economic cost and environmental metrics such as GHG emissions . Figure shows a pictorial representation of the review content presented in this section.…”
Section: Industrial Urban Symbiosis: the Sustainability Dimension Of Smart Manufacturingmentioning
confidence: 99%
“…Triantafyllidis et al developed the platform named as resilience.io to evaluate urban infrastructural projects. In this twofold study, agent‐based models were first devised to model the dynamic population behaviors and obtain the estimated demand of resources, followed by mixed‐integer programming to determine the optimal investment and operating solutions, accounting for both economic cost and environmental metrics such as GHG emissions . Figure shows a pictorial representation of the review content presented in this section.…”
Section: Industrial Urban Symbiosis: the Sustainability Dimension Of Smart Manufacturingmentioning
confidence: 99%
“…The nexus approach and circular planning for WEF sectors can increase resource flow capacity, reduce consumption, optimize production at local and regional levels, and add value to the WEF supply chain. Such integration optimizes planning for the use of resources, contributing to greater efficiency in industrial processes and infrastructure development, with consequent reductions in carbon emissions and waste generation (Lehmann, 2018;Feng et al, 2020). Local, regional, and national organizations can promote integrated planning through circular economy principles and the WEF nexus approach, focusing on improvements at the micro-meso-and macro-scales.…”
Section: Trend 3 (2019): Nexus Governance and Policy Integrationmentioning
confidence: 99%
“…However, with the conceptualizations of the W-E-F nexus becoming increasingly complex and incorporating a plurality of various data, comprehensive quantitative analyses of dependencies and interactions grow more difficult. We found that most nexus analyses were conducted at regional or national levels, and their scope was highly dependent on the availability of data, national-level policy goals and metrics [38].…”
Section: W-e-f Nexus Modelsmentioning
confidence: 99%